Estimates of Upper Bound for Differentiable Functions Associated with k-Fractional Integrals and Higher Order Strongly s-Convex Functions. (3rd July 2020) - Wu, Shanhe; Awan, Muhammad Uzair; Javed, Zakria
Abstract : In this paper, we establish two integral identities associated with differentiable functions and the k -Riemann-Liouville fractional integrals. The results are then used to derive the estimates of upper bound for functions whose first or second derivatives absolute values are higher order strongly s -convex functions.